The Sustainability of Women's Leadership in Maengket Makamberu Performance - Rattu, Jultje Aneke (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
Maengket Makamberu is one of many oral traditions that is often performed to introduce Minahasan ethnic identity, so people who know Minahasa usually know it. Althoughsome forms have already changed, Minahasan ethnic peculiarity remains. From observations on several occasions of some groups in Minahasan communities, it appeared that although some elements have changed, several other elements are still being maintained. One of the elements that still sustains its quite dominant existence is women’s leadership in both the overall performance (in literature, music, and dance) and the vocal music. The sustained element becomes the uniqueness of Minahasan ethnic’s performance. This phenomenon attracted the author to do deeper research into the mentalité behind it. Further, the author examined the performance in relation to previous developments. The development was the sustainability of tradition passing down orally from Minahasan people’s ancestors (from several generations earlier) to the next generations. This study focused on verbal, non-verbal, material texts, co-text and contexts. The above phenomenon led to the following research questions: how Maengket Makamberu sustains its existence in the changes of performance’s context and how women’s leadership of Minahasan ethnic sustains its existence in today’s Minahasan groups. To answer the research questions above, the study was conducted with two objectives. The first was to show forms of the performance in accordance with its context by analyzing the forms that were influenced by culture, society, situation, and ideology. The second was to show women’s leadership sustained in Minahasan performance by analysing women’s leadership in text and cotext related to context of performance. This study used ethnography method preceded by the collection of existing data. Empirically, it found an interesting phenomenon, a cultural distinctiveness of society. The concept sustained in the performance is a religious and democratic Walian or woman leader. The performances are different because of the cultural, social, situational, and ideological context. However, generally they have narrative and formal structures surviving until today. They carry Minahasan mentalité that has manifest functions (poetic, emotive, conative, referential) and latent ones (religious, social, knowledge/education, culture, entertainment). They are documentations to awaken and preserve Minahasan religious values as well as to endow and preserve the sustainability of Minahasan women's leadership.